MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA BILANGAN BULAT MENGGUNAKAN PENDEKATAN PAKEM PADA SISWA KELAS IV SDN 8 GEDUNG AIR - Menerfah, Ros Aini (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The selection of the title of this study is due to the problem of the low activity and achievement of mathematics learning especially integer count operations in Mathematics class IV students. The purpose of this study is to describe the increase in activity and learning achievement of integers in Mathematics in Elementary School Class IV Semester 1, using the PAKEM approach. The method used in this research is Classroom Action Research (CAR). The subjects of the study were the fourth grade students of SDN 8 Air Bandar Bandar Building Semester 1 2018/2019 Academic Year. which numbered 34 students. Data obtained from observers observation sheet notes on the learning process planned by researchers, observation sheets of learning activities and test sheets to determine learning achievement. Data were analyzed with simple statistics, namely percentages. Based on the findings and results of the discussion for 3 cycles, the increase in students' learning activities in Cycle I reached 56%, Cycle II reached 76%, Cycle III reached 85%. Learning achievement Cycle I Completed 52%, Cycle II Completed 86% Cycle III 100% and observers observing in partnership with researchers showed good average criteria. The conclusion of the study is that the use of the PAKEM approach can increase the activity and learning achievement of integer mathematics in fourth grade students of SDN 8 Gedong Air Bandar Lampung.